Pengaruh Keterampilan Guru Dalam Manajemen Kelas Terhadap Hasil Belajar Peserta Didik di Sekolah Dasar - Amanda, Yulistika; Purba, Putri Bunga Debi; Fahma, Putri Nur; Syahrial, Syahrial (Trapsila: Jurnal Pendidikan Dasar, 2024)
This research aims to determine whether good classroom management can improve student learning outcomes. The type of research used is qualitative with a literature study method using various sources such as books, journals and other sources. Data analysis techniques in literature study research go through three stages, namely organize, synthesize and identify. Data collection used in this research comes from the results of research that has been carried out and published in online journals. The analysis method used uses journal content analysis. The role of teachers in teacher management is very important, especially in the learning process. Teachers must be dedicated to creating a conducive, effective and optimal learning environment. This includes fostering sustainable learning, improving cognitive, effective and psychomotor learning, as well as fostering positive interactions between students, teachers and their environment. The impact of teacher management on student learning outcomes is quite large because it can create a more effective learning environment. Therefore, teachers must prioritize teacher management to ensure the best learning outcomes for their students. Keywords: Education, Classroom Management, Learning Outcomes, Teacher.